2018
DOI: 10.1002/14651858.cd010821.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrostimulation for adults with chronic obstructive pulmonary disease

Abstract: NMES, when applied in isolation, increased quadriceps force and endurance, 6MWD and time to symptom limitation exercising at a submaximal intensity, and reduced the severity of leg fatigue on completion of exercise testing. It may increase VO, but the true effect on this outcome measure could be trivial. However, the quality of evidence was low or very low due to risk of bias within the studies, imprecision of the estimates, small number of studies and inconsistency between the studies. Although there were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 82 publications
0
40
1
4
Order By: Relevance
“…The findings were that NMES in isolation versus usual care increased quadriceps function (strength and endurance), functional exercise performance and reduced the severity of leg fatigue. They also concluded that there were no additional effects in quadriceps strength of NMES on top of regular exercise training, but functional exercise performance increased [82]. However, in this review, no distinction has been made in patients who are capable of regular exercise training like endurance training and patients who were hospitalized because of an acute exacerbation [82].…”
Section: Neuromuscular Electrical Stimulation In Patients With Copdmentioning
confidence: 90%
See 1 more Smart Citation
“…The findings were that NMES in isolation versus usual care increased quadriceps function (strength and endurance), functional exercise performance and reduced the severity of leg fatigue. They also concluded that there were no additional effects in quadriceps strength of NMES on top of regular exercise training, but functional exercise performance increased [82]. However, in this review, no distinction has been made in patients who are capable of regular exercise training like endurance training and patients who were hospitalized because of an acute exacerbation [82].…”
Section: Neuromuscular Electrical Stimulation In Patients With Copdmentioning
confidence: 90%
“…In 2018, Hill and colleagues conducted a Cochrane review in which 16 studies incorporating 267 patients with COPD were included [82]. Seven studies analyzed the effects of NMES versus usual care and nine studies analyzed the effects of NMES combined with regular exercise training versus exercise training alone.…”
Section: Neuromuscular Electrical Stimulation In Patients With Copdmentioning
confidence: 99%
“…The neuromuscular electrical stimulation (NMES) can be used to increase peripheral muscle strength and/or endurance in patients who are unable to achieve adequate intensity during conventional aerobic training (e.g., very severe COPD and/or during severe exacerbations of the disease) 102 . The NMES generates similar effects as resistance training on exercise capacity, muscle strength BARCELONA RESPIRATORY NETWORK and symptoms 103,104 . Although this intervention seems to be able to induce increases in the cross-sectional area 105 , no changes were observed in the relative fibre distribution or capillarity 104 .…”
Section: Neuromuscular Electrical Stimulation (Nmes)mentioning
confidence: 98%
“…Although this intervention seems to induce increments in the cross-sectional area 105 , no changes were observed in the relative fibre distribution or capillarisation 104 . The effect of NMES at micro-structural level is still unclear, partly due to the heterogeneity of the protocols used 103 . Therefore, more studies with higher methodological quality are necessary to investigate the possible changes in muscle structure as well as to highlight which is the profile of the patients that would benefit the most from this type of intervention.…”
Section: Neuromuscular Electrical Stimulation (Nmes)mentioning
confidence: 99%
“…To run a hospital‐based pulmonary rehabilitation programme for the most complex patients with COPD, the involvement of multiple, skilled healthcare professionals with COPD‐specific knowledge seems imperative . For example, physiotherapists should be aware of the various treatment possibilities, including neuromuscular electrical stimulation and exercise training combined with non‐invasive ventilation; or dieticians should be trained to modulate patient's nutritional pattern, taking body composition abnormalities (i.e. cachexia and obesity) and cardiovascular risk factors (i.e.…”
Section: Settings For Pulmonary Rehabilitationmentioning
confidence: 99%